Empowering Women with Kudumbashree – A Study of Vamanapuram Block in Thiruvananthapuram District - Kerala State - M. S. Shibi Chandradas (International Journal of Recent Research Aspects, 2018)
This study points out the role of Kudumbashree and its impact on women empowerment in Kerala with special reference to Vamanapuram block in Thiruvananthapuram District. Kudumbshree is a practical model for strengthening the Self Help Group (SHG) based poverty alleviation programme. Questionnaire and interview were used for collecting the data. The study found that, Kudumbashree leads to sustainable social, economic development of women and a direct impact on their living status, educational, nutritional and health needs of their children, positively. The purpose of the Kudumbashree scheme is to improve the standard of living of poor women in rural areas by setting up micro-credit and productive enterprises. . Kudumbashree was launched by the Government of Kerala in 1998 with an aim to eradicate poverty in rural and urban areas of Kerala through community development schemes, under the leadership of Local Self Governments. It is now considered as one of the largest women-empowering projects in India. The programme is linked to local self-government institution and it makes all the effort to alleviate poverty through an integrated approach involving effective union of resources and action.